Managing Scale Insects and Mealybugs on Turfgrass - Adam G. Dale (EDIS)
This 8-page fact sheet describes the types of scale insects and mealybugs that can become pests in turf, explains the damage they do, and lists management techniques to control them. Written by Adam Dale and published by the UF Department of Entomology and Nematology, February 2017.